Integrated IOT Based System for Accident Reporting and Automatic Toll Collection using RFID - P. Sharvani, Mrs.P. N. Ramya (International Journal of Advanced Science and Technology, 2020)
In a developing nation like India, with development inside the transportation generation and upward push inside the total variety of automobiles road accidents boom hastily and there’s also tax gathering issues. So a solution for both problems is discussed and implemented. For the toll tax collection related issues an automatic tax collecting system is developed with the use of RFID Technology. Whenever a RFID reader receives a signal from its associated RFID tag, checks for the authorization of vehicle and collect the tax accordingly. And for accident related issues the implemented system has two Phases-Accident Detection and Accident Prevention. To avoid Accidents, we are using Alcohol sensor to detect whether the person is alcoholic or not. If any accidents occur on highways immediately MEMS sensor detect the tilted angle of vehicle and when the vehicle is tilted more, then the sensor value becomes high and intimate the camera to capture the images and send the images to the registered mail id and also send the GPS location to registered mobile number through SMS.